FEATURES OF MONOCYTE POLARIZATION AT DIFFERENT OUTCOMES IN WOMEN WITH RECURRENT MISCARRIAGE - E. V. Grigushkina; N. Yu. Sotnikova; N. V. Kroshkina; A. I. Malyshkina; I. E. Talanova (Медицинская иммунология, 2021)
Currently, in the pathogenesis of recurrent miscarriage, a special role is given to immunological factors, in particular the role of innate immunity. The aim of the study was to assess the relative content of monocytes in the peripheral blood producing IL-4, IL-6, IL-10, IFNγ, as well as to identify new criteria for predicting the outcome of pregnancy in women with the threat of early termination and recurrent miscarriage. Materials and methods. 88 pregnant women at 5-12 weeks’ gestation were examined, the main group consisted of 59 women with recurrent miscarriage and threatened miscarriage at the time of the study, the control group – 29 women with uncomplicated pregnancy without recurrent miscarriage. The main group, depending on the outcomes of pregnancy, was subdivided into subgroups: subgroup I – 42 women whose pregnancy ended in timely delivery, subgroup II – 8 women with preterm labor, subgroup III – 9 women with abortion up to 22 weeks (spontaneous miscarriage and non-developing pregnancy). In the control group, all women had a timely delivery. Research material – peripheral venous blood. The relative content of IL-4+, IL-6+, IL-10+, IFNγ+ monocytes was assessed on a FACSCanto II flow cytometer using monoclonal antibodies. Statistical data processing was carried out using a package of standard applied programs. Results. In the group of women with recurrent miscarriage and threatened miscarriage, the relative content of IL-10+ and IL-4+ monocytes was reduced and the content of IL-6+ monocytes was increased compared to the control group (p = 0.0001 in all cases). There were no statistically significant differences in the content of IFNγ+ monocytes in the compared groups (p = 0.069). With a relative content of IL-4+ monocytes equal to 26.7% or less, preterm labor is predicted. With a relative content of IL-10+ monocytes equal to 27.0% or less, abortion (spontaneous miscarriage or miscarriage) is predicted in gestational age up to 22 weeks. An increase in the ratio of IFNγ+/ IL-4+, IFNγ+/IL-10+, IL-6+/IL-4+, IL-6+/IL-10+ monocytes was found in the main group (p < 0.0001 in all cases ). Conclusions. In women with recurrent miscarriage in all subgroups, the level of M1 monocytes prevailed over the level of M2 monocytes. The data obtained allowed the development of new prognostic criteria for termination of pregnancy up to 22 weeks and premature birth.